Neuroacanthocytosis syndromes - Danek, Adrian. (Springer Netherlands, 2005)
Neuroacanthocytosis syndromes is the first comprehensive review of a field that has not yet received the attention it deserves. Affecting the brain as well as the circulating red cells, these multi-system disorders in the past had often been mistaken for Huntington's disease. Recent breakthroughs have now identified the molecular basis of several of these. This volume grew out of the first international scientific meeting ever devoted to neuroacanthocytosis and provides in-depth information about the state of the art. Its thirty chapters were written by the leading authorities in the field to cover the clinical as well as the basic science perspective, including not only molecular genetics but also experimental pharmacology and cell membrane biology, among others. The book vehemently poses the question of how the membrane deformation of circulating red blood cells relates to degeneration of nerve cells in the brain, the basal ganglia, in particular. It provides a wealth of data that will help to solve an intriguing puzzle and ease the suffering of those affected by one of the neuroacanthocytosis syndromes. Neuroacanthocytosis syndromes: what links red blood cells and neurons? -- Clinical context -- The differential diagnosis of neuroacanthocytosis: an overview -- Acanthocytes and disorders of lipoprotein metabolism -- Levine-critchley syndrome of neuroacanthocytosis: a clinical review -- Chorea-acanthocytosis with the ehime-deletion mutation -- McLeod syndrome: a clinical review -- Autosomal-dominant chorea-acanthocytosis: report of a family and neuropathology -- Acanthocytes in pantothenate kinase associated neurodegeneration -- Diagnostic test for neuroacanthocytosis: quantitative measurement of red blood cell morphology -- Differential diagnosis of serum creatine kinase elevation -- Organ involvement -- Pathology of neuroacanthocytosis and of huntington’s disease -- Cognitive and neuropsychiatric findings in mcleod syndrome and in chorea-acanthocytosis -- Epilepsy in neuroacanthocytosis -- Sleep features in chorea-acanthocytosis -- Neuromuscular findings in eight italian families with neuroacanthocytosis -- Cardiac involvement in the neuroacanthocytosis syndromes -- Basic science -- Erythrocyte membrane abnormalities in neuroacanthocytosis: evidence for a neuron-erythrocyte axis? -- Erythrocyte membrane anion exchange abnormalities in chorea-acanthocytosis: the band 3 network -- The spectrum of mutations and possible function of the CHAC gene -- Immunohematology of the kell and KX blood group systems -- C. elegans as a disease model for neuroacanthocytosis -- The kell blood group protein, its relation to XK and its function as an endothelin-3-converting enzyme -- Endothelins as basal ganglia transmitters -- Substrates for transglutaminase-catalyzed cross-linking: relevance to pathogenesis of huntington’s disease and chorea-acanthocytosis -- Huntington’s disease animal models: what lessons can be learned for research on neuroacanthocytosis syndromes? ... Motor deficits as biomarkers in huntington’s disease: perspectives for neuroacanthocytosis syndromes -- - Treatment -- Treatment options in Huntington’s disease -- Is surgical treatment an option for chorea-acanthocytosis? -- The potential for gene therapy of neurodegenerative disorders -- Summary -- Research agenda in neuroacanthocytosis.